Nonintravesical Interventions for Preventing Intravesical Recurrence in Patients With Nonmuscle-Invasive Bladder Cancer: A Systematic Review and Meta-Analysis - Tsuboi, Ichiro; Matsukawa, Akihiro; Kardoust Parizi, Mehdi; Schulz, Robert J; Mancon, Stefano; Fazekas, Tamás; Miszczyk, Marcin; Cadenar, Anna; Laukhtina, Ekaterina; Rajwa, Pawel; Kawada, Tatsushi; Katayama, Satoshi; et al. (Clinical genitourinary cancer, 2025)
Despite currently used intravesical therapies in non-muscle-invasive bladder cancer (NMIBC), the rate of intravesical recurrence remains very high. We aimed to evaluate the effectiveness of adding nonintravesical interventions to standard intravesical therapies to prevent intravesical recurrence. In April 2024, 3 databases were queried for prospective studies evaluating nonintravesical interventions in addition to standard intravesical therapies for NMIBC (CRD42024490988). The primary outcome was intravesical recurrence-free survival (iRFS). Standard pairwise meta-analyses were performed using hazard ratios (HR) and 95% confidence intervals (95% CI) with a random-effects model. We identified 18 eligible studies (14 RCTs and 4 prospective trials) comprising 4,593 NMIBC patients, which investigated pharmacological interventions (eg, selenium, vitamins, Lactobacillus casei, celecoxib, metformin, mistletoe lectin) and lifestyle modifications (diet). The addition of Lactobacillus casei significantly improved iRFS (HR: 0.50; 95% CI: 0.34-0.73; P < .001). A high western diet pattern significantly worsened iRFS (HR:1.48, 95%CI:1.06-2.06, P = .03). The other nonintravesical interventions were not associated with iRFS. Our comprehensive review of the published literature highlights the need for further research into the efficacy of nonvesical interventions for NMIBC. While Lactobacillus was shown to improve iRFS in 2 RCTs, additional high-quality randomized studies are required to evaluate the effectiveness of other interventions.
Keywords: Lactobacillus casei; aplikace intravezikální; Vitamins; Urinary Bladder Neoplasms; Non-muscle-invasive bladder cancer; Diet; Humans; Neoplasm Recurrence, Local; Administration, Intravesical; Lacticaseibacillus casei; lokální recidiva nádoru; Celecoxib; nádory močového měchýře; lidé